Construction of a Green and Sustainable Cultivation Model for Annual Forage Oat in Alpine Ecosystems: Optimization and Synergistic Mechanisms of Combined Application of Microbial Fertilizers and Organic Fertilizers - Zongcheng Cai; Jianjun Shi; Liangyu Lv; Pei Gao; Hairong Zhang; Fayi Li; Shouquan Fu; Qingqing Liu; Shancun Bao (Plants)
The aim of this study was to establish a green fertilization regime combining microbial fertilizers and livestock manure organic fertilizer for two dominant oat cultivars (Avena sativa L. ‘Baiyan No.7’ and ‘Qingyin No.2’) in alpine ecosystems, providing technical support for sustainable forage production systems in grassland pastoral areas of the Qinghai-Tibet Plateau. The experiment was conducted following the principles of a randomized block design, with five application rates each of effective microbial fertilizer (EM) and compound microbial fertilizer (FH) applied in combination with 18,000 kg·hm−2 of livestock manure organic fertilizer to systematically analyze their effects on oat agronomic traits, yield quality, and soil health. Key results demonstrated the following: for Avena sativa ‘Baiyan No.7’, effective microbial fertilizer (EM) application at 15.00 kg·hm−2 significantly increased plant height by 41.29% (p < 0.05), while effective microbial fertilizer (EM) at 18.75 kg·hm−2 optimized stomatal conductance and the transpiration rate by 73.29% and 46.42%, respectively. For Avena sativa L.‘Qingyin No.2’, compound microbial fertilizer (FH) application at 22.50 kg·hm−2 enhanced plant height and relative chlorophyll content (SPAD value) of the flag leaf by 50.92% and 47.75%. Yield analysis revealed that compound microbial fertilizer (FH) application at 22.50 kg·hm−2 increased the fresh forage yield and dry matter yield of ‘Baiyan No.7’ by 34.53% and 38.64%, respectively, with crude protein content reaching 11.02%. Maximum fresh forage yield (38,073.00 kg·hm−2) for ‘Qingyin No.2’ was achieved with effective microbial fertilizer (EM) at 11.25 kg·hm−2, while compound microbial fertilizer (FH) at 22.50 kg·hm−2 facilitated synergistic accumulation of crude protein (12.57%) and soluble sugars (15.58%). Soil organic carbon increased by 28.85% under compound microbial fertilizer (FH) at 22.50 kg·hm−2 for ‘Baiyan No.7’, and by 26.21% under effective microbial fertilizer (EM) at 18.75 kg·hm−2 for ‘Qingyin No.2’. In summary, a cultivar-specific green fertilization system was established: for Avena sativa L. ‘Baiyan No.7’: the application of 18.75 kg·hm−2 effective microorganisms fertilizer with 18,000 kg·hm−2 organic manure; for Avena sativa L. ‘Qingyin No.2’: the application of 22.50 kg·hm−2 compound microbial fertilizer with 18,000 kg·hm−2 organic manure. This system achieved triple sustainability objectives in alpine oat production: enhancing yield, optimizing quality, and improving soil health.